A Review of Urban Water Body Challenges and Approaches: (1) Rehabilitation and Remediation. Issue 1 (24th January 2014) - Hughes, Robert M.; Dunham, Susie; Maas‐Hebner, Kathleen G.; Yeakley, J. Alan; Schreck, Carl; Harte, Michael; Molina, Nancy; Shock, Clinton C.; Kaczynski, Victor W.; Schaeffer, Jeff
Abstract: We review how urbanization alters aquatic ecosystems, as well as actions that managers can take to remediate urban waters. Urbanization affects streams by fundamentally altering longitudinal and lateral processes that in turn alter hydrology, habitat, and water chemistry; these effects create physical and chemical stressors that in turn affect the biota. Urban streams often suffer from multiple stressor effects that have collectively been termed an "urban stream syndrome, " in which no single factor dominates degraded conditions. Resource managers have multiple ways of combating the urban stream syndrome. These approaches range from whole‐watershed protection to reach‐scale habitat rehabilitation, but the prescription must be matched to the scale of the factors that are causing the problem, and results will likely not be immediate because of lengthy recovery times. Although pristine or reference conditions are far from attainable, urban stream rehabilitation is a worthy goal because appropriate actions can provide ecosystem improvements as well as increased ecosystem service benefits for human society.